Predatory activity and passage of six nematophagous fungi species in gastrointestinal tract of trichostrongylide-infected sheep - Xue, Ya-Juan; Li, Er-Le; Wang, Ai-Hong; Cai, Kui-Zheng (Biocontrol science and technology, 2018)
With the development of anthelmintic resistance of parasitic nematodes, screening the potential of predatory fungi candidates by in vitro and in vivo assay is necessary for biocontrol of parasitic nematodes in sheep. Fifteen native isolates of fungi species of six predators were evaluated through in vitro and in vivo experiment to evaluate the capacity of passing through the gastrointestinal tract of sheep. The results of the in vitro experiment showed that the reduction percentages of the third-stage larvae (L3) of trichostrongylides in faeces were 97.02-98.49% for five isolates of Arthrobotrys (Monacrosporium) sinense; 83.47-99.12% for three isolates of Arthrobotrys oviformis; 80.00-97.41% for four isolates of Arthrobotrys conoides; and 99.18%, 77.56%, and 75.72% for one isolate of Arthrobotrys microscaphoides, Arthrobotrys salina, and Dactylellina leptospora, respectively. In the in vivo assay, the results exhibited that the larval recoveries in faeces were significantly decreased (p < .05), and L3 reduction percentage ranged from 37.84% to 86.93% for all fungal isolates tested, except for one isolate of D. leptospora. After fungal treatment (within 24 h) of one isolate of A. salina, although the efficacy against L3 was 43.83%, tested fungus was detected in the faeces. The remaining isolates, except one isolate of D. leptospora and one isolate of A. conoides, were positive for either L3 reduction or fungal survival in faeces. The present study showed that nematophagous fungi could survive in the passage through the alimentary tract of sheep and should be potential candidates as a feed supplement.